2011
DOI: 10.1002/em.20671
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory Pig‐a gene mutation assay trial: Studies of 1,3‐propane sultone with immunomagnetic enrichment of mutant erythrocytes

Abstract: An international collaborative trial was established to systematically investigate the merits and limitations of a rat in vivo Pig-a gene mutation assay. The product of this gene is essential for anchoring CD59 to the plasma membrane, and mutations in this gene are identified by flow cytometric quantification of circulating erythrocytes without cell surface CD59 expression. Initial interlaboratory data from rats treated with several potent mutagens have been informative, but the time required for those flow cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 22 publications
3
23
0
3
Order By: Relevance
“…Immunomagnetic separation provided an effective and efficient means to enrich the proportion of mutant cells and allow the enumeration of larger numbers of rare mutant phenotype cells. Thus, as with the analogous rodent blood assay, immunomagnetic depletion of wild-type cells prior to flow cytometry facilitated evaluation of magnitudes-greater numbers of cells than would have otherwise been possible [Dertinger et al, 2011b,c; 2012]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunomagnetic separation provided an effective and efficient means to enrich the proportion of mutant cells and allow the enumeration of larger numbers of rare mutant phenotype cells. Thus, as with the analogous rodent blood assay, immunomagnetic depletion of wild-type cells prior to flow cytometry facilitated evaluation of magnitudes-greater numbers of cells than would have otherwise been possible [Dertinger et al, 2011b,c; 2012]. …”
Section: Discussionmentioning
confidence: 99%
“…This low baseline frequency led us to utilize immu-nomagnetic depletion of wild-type cells prior to flow cytometric analysis in order to enrich samples for mutant phenotype cells, as has been described for rat blood [Dertinger et al, 2011b,c, 2012]. In this manner, data acquisition rates and the number of cell equivalents evaluated per sample are enhanced dramatically.…”
Section: Introductionmentioning
confidence: 99%
“…Treatments were based on previous studies (11-13) with male rats that showed these dose levels are tolerated and significant increases in Pig-a mutant phenotype cells are induced.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, these data provided the impetus for establishing a method to dramatically increase the number of cells evaluated per sample through the use of immunomagnetic separation technology [21]. Stage IV studies have been conducted with these updated methods and demonstrate improved statistical power [21,28,29], but only a fraction of the completed work has been published or available to the Workgroup in a form that could be used to assess intra-and interlaboratory reproducibility.…”
Section: Intra/inter-laboratory Reproducibilitymentioning
confidence: 97%